Optical black holes and solitons - Westmoreland, Shawn Michael (Kansas State University, 2010)
We exhibit a static, cylindrically symmetric, exact solution to the Euler-Heisenberg field equations (EHFE) and prove that its effective geometry contains (optical) black holes. It is conjectured that there are also soliton solutions to the EHFE which contain black hole geometries.
Keywords: Optical black holes; Solitons; Effective geometries; Nonlinear PDEs; Nonlinear electrodynamics; Euler-Heisenberg Lagrangian; Mathematics (0405)